Rate of perceived exertion changes non- monotonically in constant-ower exercise until exhaustion - Balagué, N.; Aragonés, D.; Hristovski, R.; Tenenbaum, G.; Garcia, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Rate of perceived exertion (RPE) increases linearly with workload in incremental exercises; however, RPE changes under constant workload are unclear. The aim of this study was to reveal and study the non-monotonic changes of RPE in constant-power exercise performed until volitional exhaustion. Methods: A pilot study and a main experiment were carried out. The same cycling test (Sport Excalibur 925900) was performed in both cases. After a progressive warming-up, twenty seven participants pedaled at a constantpower (RPE= 15, 70 RPM) until volitional exhaustion. The pilot study compared the cardinal RPE dynamics during the exercise using three different measurement strategies: (1) CR10 scale sampling RPE every min (n = 9), (2) CR10 scale sampling every 15 sec (n = 8), and (3) RPE 6-20 scale sampling every 15 sec (n = 10). In the main experiment 13 participants reported their ordinal RPE non-monotonous changes (increases/decreases) when noticed during the same cycling exercise. The data series of the participants were divided into 10 nonoverlapping temporal windows to obtain the RPE non-monotonic changes probabilities. Results: In the pilot study, where 3 measurement strategies were used, 10%, 30% and 60% of the participants, respectively, presented non-monotonic changes in RPE. In the main experiment all participants showed such RPE non-monotonic changes, which were identified in three different time scales (15 sec, 30 sec, min). The 10 exertion time windows repeated-measures Friedman ANOVA (N = 13, df = 9) revealed a significant effect, ÷2 (13, 9) = 41.41 p < .0001, of exertion time on RPE non-monotonic changes probabilities. Three effort phases were distinguished: The beginning and ending were characterized by RPE monotonic changes and the mid phase by RPE non-monotonic changes. Discussion: The findings, relevant for a nonlinear dynamic approach to exercise tolerance, reveal the existence of non-monotonic changes in RPE during constant-power exercise, highlight the interest of its evaluation for recognising non-invasively effort tolerance phases and provide information for clarifying the role assigned to perceived exertion in previous psychobiological models.